2014
DOI: 10.2147/cia.s67052
|View full text |Cite
|
Sign up to set email alerts
|

Age as a risk factor for acute mountain sickness upon rapid ascent to 3,700 m among young adult Chinese men

Abstract: BackgroundThe aim of this study was to explore the relationship between age and acute mountain sickness (AMS) when subjects are exposed suddenly to high altitude.MethodsA total of 856 young adult men were recruited. Before and after acute altitude exposure, the Athens Insomnia Scale score (AISS) was used to evaluate the subjective sleep quality of subjects. AMS was assessed using the Lake Louise scoring system. Heart rate (HR) and arterial oxygen saturation (SaO2) were measured.ResultsResults showed that, at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…In contrast, exclusion of the study by You et al 31 increased the pooled OR to 0.92 (95% CI = 0.78-1.09). When we calculated the pooled OR based on the four studies available that provided the results of multivariate risk modeling including smoking , 25,35,36,38 this was a weakly positive (11% increase) risk factor for AMS with wide confidence intervals (OR = 1.13; 95% CI = 0.53-2.41).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, exclusion of the study by You et al 31 increased the pooled OR to 0.92 (95% CI = 0.78-1.09). When we calculated the pooled OR based on the four studies available that provided the results of multivariate risk modeling including smoking , 25,35,36,38 this was a weakly positive (11% increase) risk factor for AMS with wide confidence intervals (OR = 1.13; 95% CI = 0.53-2.41).…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies reported different results. Tang et al [ 49 ] suggested that the elderly were more sensitive to AMS, whereas Hackett et al [ 2 , 22 , 32 ] reported opposite findings, suggesting that older age is protective against AMS. In addition, some studies indicated that age has no relationship with AMS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to identify risk factors that can be used to predict AMS susceptibility. A substantial number of studies have shown that age [8, 9], body mass index (BMI) [9, 10], arterial oxygen saturation [11], sleep quality [12] and gender [13, 14] are correlated with AMS susceptibility. However, other studies have found that these factors do not play a role in AMS development [15].…”
Section: Introductionmentioning
confidence: 99%